2020
DOI: 10.1101/2020.06.30.175695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Infection of Pluripotent Stem Cell-derived Human Lung Alveolar Type 2 Cells Elicits a Rapid Epithelial-Intrinsic Inflammatory Response

Abstract: ABSTRACTThe most severe and fatal infections with SARS-CoV-2 result in the acute respiratory distress syndrome, a clinical phenotype of coronavirus disease 2019 (COVID-19) that is associated with virions targeting the epithelium of the distal lung, particularly the facultative progenitors of this tissue, alveolar epithelial type 2 cells (AT2s). Little is known about the initial responses of human lung alveoli to SARS-CoV-2 infection due in part to inability to access these cell… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
102
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 42 publications
19
102
2
1
Order By: Relevance
“…These findings are consistent with the well-established notion that ALI conditions favor growth as pseudo-stratified mucociliary epithelium (Dvorak et al, 2011;Prytherch et al, 2011). As an alternative model for use as monolayers for viral infection, we developed hiPSC-derived AT2 cells and alveolospheres (Fig 3C), using established protocols (Huang et al, 2020). Because they were grown in the presence of CHIR99021 (an aminopyrimidine derivate that is a selective and potent Wnt agonist) (Abdelwahab et al, 2019;, which probably inhibits the AT2→AT1 differentiation, these monolayers were enriched for AT2 and devoid of AT1 cells (Fig 3D).…”
Section: Organoid Cellularity Resembles Tissue Sources In 3d Culturessupporting
confidence: 87%
See 2 more Smart Citations
“…These findings are consistent with the well-established notion that ALI conditions favor growth as pseudo-stratified mucociliary epithelium (Dvorak et al, 2011;Prytherch et al, 2011). As an alternative model for use as monolayers for viral infection, we developed hiPSC-derived AT2 cells and alveolospheres (Fig 3C), using established protocols (Huang et al, 2020). Because they were grown in the presence of CHIR99021 (an aminopyrimidine derivate that is a selective and potent Wnt agonist) (Abdelwahab et al, 2019;, which probably inhibits the AT2→AT1 differentiation, these monolayers were enriched for AT2 and devoid of AT1 cells (Fig 3D).…”
Section: Organoid Cellularity Resembles Tissue Sources In 3d Culturessupporting
confidence: 87%
“…Although somewhat unexpected, the role of AT1 pneumocytes in mounting innate immune responses has been documented before in the context of bacterial pneumonia (Wong and Johnson, 2013;Yamamoto et al, 2012). In work (Huang et al, 2020) that was published during the preparation of this manuscript, authors used long-term ALI models of hiPSC-derived AT2 monolayers (in growth conditions that inhibit AT2→AT1 differentiation, as we did here for our AT2 model) and showed that SARS-CoV-2 induces iAT2-intrinsic cytotoxicity and inflammatory response, but failed to induce type 1 interferon pathways (IFN α/β). It is possible that prolonged culture of iAT2 pneumocytes gives rise to some DATPs but cannot robustly do so in the presence of inhibitors of AT1 differentiation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In line with this argument, examining drug activity in physiologically relevant cells is essential for prospecting in vivo antiviral efficacy. Human airway epithelial cells in an air-liquid interface culture [ 86 ] and human induced pluripotent stem cell-derived lung epithelial cells [ 87 , 88 ] will provide more physiological relevance to the study of SARS-CoV-2 infections. In addition, human organoids of a variety of tissues such as lung, intestine, blood vessel, kidney, liver, and brain were reported to be susceptible to infection by SARS-CoV-2 or its pseudovirus [ [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] ].…”
Section: Cell Culture Approachmentioning
confidence: 99%
“…Based on available literature [7], we employed the directed differentiation technique to derive lung epithelial lineage from human induced pluripotent stem cells (hiPSC), to serve as a human model, using a three-step protocol (Fig. 1A) [8,9].…”
mentioning
confidence: 99%